Complexation of Np(V) with the dicarboxylates, malonate, and succinate: complex stoichiometry, thermodynamic data, and structural information - Maiwald, Martin M.; Müller, Katharina; Heim, Karsten; Rothe, Jörg; Dardenne, Kathy; Rossberg, André; Koke, Carsten; Trumm, Michael; Skerencak-Frech, Andrej; Panak, Petra (Inorganic chemistry, 2021)
The complexation of Np(V) with malonate and succinate is studied by different spectroscopic techniques, namely, attenuated total reflection Fourier transform infrared (ATR FT-IR) and extended X-ray absorption fine-structure (EXAFS) spectroscopy, as well as by quantum chemistry to determine the speciation, thermodynamic data, and structural information of the formed complexes. For complex stoichiometries and the thermodynamic functions (log βn°(Θ), ΔrHn°, ΔrSn°), near infrared absorption spectroscopy (vis/NIR) is applied. The complexation reactions are investigated as a function of the total concentration of malonate ([Mal2-]total) and succinate ([Succ2-]total), ionic strength [Im = 0.5-4.0 mol kg-1 Na+(Cl-/ClO4-)], and temperature (Θ = 20-85 °C). Besides the solvated NpO2+ ion, the formation of two Np(V) species with the stoichiometry NpO2(L)n1-2n (n = 1, 2, L = Mal2-, Succ2-) is observed. With increasing temperature, the molar fractions of both complex species increase and the temperature-dependent conditional stability constants log βn′(Θ) at given ionic strengths are determined by the law of mass action. The log βn′(Θ) are extrapolated to IUPAC reference-state conditions (Im = 0) according to the specific ion interaction theory (SIT), revealing thermodynamic log βn°(Θ) values. For all formed complexes, [NpO2(Mal)−: log β1°(25 °C) = 3.36 ± 0.11, NpO2(Mal)23-: log β2°(25 °C) = 3.95 ± 0.19, NpO2(Succ)−: log β1°(25 °C) = 2.05 ± 0.45, NpO2(Succ)23-: log β2°(25 °C) = 0.75 ± 1.22], an increase of the stability constants with increasing temperature was observed. This confirmed an endothermic complexation reaction. The temperature dependence of the log βn°(T) values is described by the integrated Van’t Hoff equation, and the standard reaction enthalpies and entropies for the complexation reactions are determined. Furthermore, the sum of the specific binary ion-ion interaction coefficients Δεn°(Θ) for the complexation reactions are obtained as a function of the t from the respective SIT modeling as a function of the temperature. In addition to the thermodynamic data, the structures of the complexes and the coordination modes of malonate and succinate are investigated using EXAFS spectroscopy, ATR-FT-IR spectroscopy, and quantum chemical calculations. The results show that in the case of malonate, six-membered chelate complexes are formed, whereas for succinate, seven-membered rings form. The latter ones are energetically unfavorable due to the limited space in the equatorial plane of the Np(V) ion (as NpO2+ cation).